The Effect of Problem-Based Learning Assisted by Interactive PowerPoint on High School Students’ Creativity: A Quasi-Experimental Study - Elya Suci Nabila; Mahrus Mahrus; Anggi Fadila Cahyani; Aiman Mustafa; Arbi Arrahman (Indonesian Journal of Educational Innovation, 2026)
Science learning at the senior high school level, which remains teacher-centered, has resulted in suboptimal development of students’ creativity. This study aims to examine the effect of Problem-Based Learning (PBL) assisted by interactive PowerPoint on the creativity of tenth-grade students at SMAN 1 Labuapi in science learning. This study employed a quantitative quasi-experimental design with a nonequivalent control group. The sample consisted of 40 students, divided into an experimental class (XA) and a control class (XB), using a saturated sampling technique. Creativity data were collected using essay test instruments covering indicators of fluency, flexibility, and originality, and were analyzed using ANCOVA with pretest scores as the covariate. The results showed F = 5.577 with a significance value of 0.024 < 0.05, and the adjusted mean of the experimental class, 81.265, was higher than that of the control class, 77.472. Therefore, it can be concluded that PBL assisted by interactive PowerPoint significantly affects the creativity of tenth-grade students in science learning. These findings suggest that integrating PBL with interactive media can be an innovative alternative for science teachers to design more authentic, contextual learning experiences that foster students’ creativity in alignment with the Merdeka Curriculum.